Owen Wister papers - Wister, Owen, 1860-1938.; Wister, Owen, 1860-1938.
Correspondence, diaries and journals, family papers, drafts of articles, poems, novels, short stories, speeches, and other writings, scrapbooks, financial papers, printed matter, and other papers. Includes partial manuscript and dramatizations of Wister's best-known work, The Virginian, A Horseman of the Plains (1902) and his libretto for "Villon; a Romantic Opera in Four Acts." Family correspondents include Fanny Kemble (Wister's grandmother), Sarah Butler Wister (his mother), Mary Channing Wister (his wife), and his cousins, S. Weir Mitchell and Langdon Elwyn Mitchell.
Other correspondents include Charles Francis Adams, Henry Adams, Edward William Bok, Nicholas Murray Butler, John Jay Chapman, Joseph H. Coit, Richard Harding Davis, Charles W. Eliot, John Watson Foster, Hamlin Garland, Ernest Hemingway, Henry Lee Higginson, Oliver Wendell Holmes, Jr., M. A. De Wolfe Howe, Henry James, William James, J. J. Jusserand, Rudyard Kipling, Kirke La Shelle, Henry Cabot Lodge, Charles Eliot Norton, Walter Hines Page, Frederic Remington, Alice Repplier, Theodore Roosevelt, Henry Dwight Sedgwick, Upton Sinclair, Sir Campbell Stuart, William Howard Taft, Barrett Wendell, Edith Wharton, William Allen White, and Caspar Whitney.
Microfilm edition of scrapbooks available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Music Division.
Library of Congress Prints and Photographs Division.
Author and writer of western novels.
Collection material in English.
Keywords: Adams, Charles Francis, -- 1835-1915 -- Correspondence; Adams, Henry, -- 1838-1918 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Chapman, John Jay, -- 1862-1933 -- Correspondence; Coit, Joseph H. -- 1831-1906 -- Correspondence; Davis, Richard Harding, -- 1864-1916 -- Correspondence; Eliot, Charles William, -- 1834-1926 -- Correspondence; Foster, John Watson, -- 1836-1917 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Hemingway, Ernest, -- 1899-1961 -- Correspondence; Higginson, Henry Lee, -- 1834-1919 -- Correspondence; Holmes, Oliver Wendell, -- 1841-1935 -- Correspondence; Howe, M. A. De Wolfe -- 1864-1960 -- Correspondence; James, Henry, -- 1843-1916 -- Correspondence; James, William, -- 1842-1910 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Kemble, Fanny, -- 1809-1893 -- Correspondence; Kipling, Rudyard, -- 1865-1936 -- Correspondence; La Shelle, Kirke -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Mitchell, Langdon Elwyn, -- 1862-1935 -- Correspondence; Mitchell, S. Weir -- 1829-1914 -- Correspondence; Norton, Charles Eliot, -- 1827-1908 -- Correspondence; Page, Walter Hines, -- 1855-1918 -- Correspondence; Remington, Frederic, -- 1861-1909 -- Correspondence; Repplier, Agnes, -- 1855-1950 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Sedgwick, Henry Dwight, -- 1861-1957 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Stuart, Campbell, -- Sir, -- 1885- -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wendell, Barrett, -- 1855-1921 -- Correspondence; Wharton, Edith, -- 1862-1937 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Whitney, Caspar, -- 1862-1929 -- Correspondence; Wister, Mary Channing, -- 1869-1913 -- Correspondence; Wister, Sarah Butler, -- 1835-1908 -- Correspondence; Operas -- Librettos; Western stories; Authors